Electrophysiologic features of SYT2 mutations causing a treatable neuromuscular syndrome. (1st December 2015) - Whittaker, Roger G.; Herrmann, David N.; Bansagi, Boglarka; Hasan, Bashar Awwad Shiekh; Lofra, Robert Muni; Logigian, Eric L.; Sowden, Janet E.; Almodovar, Jorge L.; Littleton, J. Troy; Zuchner, Stephan; Horvath, Rita; Lochmüller, Hanns
Abstract : Objectives: To describe the clinical and electrophysiologic features of synaptotagmin II ( SYT2 ) mutations, a novel neuromuscular syndrome characterized by foot deformities and fatigable ocular and lower limb weakness, and the response to modulators of acetylcholine release. Methods: We performed detailed clinical and neurophysiologic assessment in 2 multigenerational families with dominant SYT2 mutations (c.920T>G [p.Asp307Ala] and c.923G>A [p.Pro308Leu]). Serial clinical and electrophysiologic assessments were performed in members of one family treated first with pyridostigmine and then with 3, 4-diaminopyridine. Results: Electrophysiologic testing revealed features indicative of a presynaptic deficit in neurotransmitter release with posttetanic potentiation lasting up to 60 minutes. Treatment with 3, 4-diaminopyridine produced both a clinical benefit and an improvement in neuromuscular transmission. Conclusion: SYT2 mutations cause a novel and potentially treatable complex presynaptic congenital myasthenic syndrome characterized by motor neuropathy causing lower limb wasting and foot deformities, with reflex potentiation following exercise and a uniquely prolonged period of posttetanic potentiation.